Multiple functionally divergent and conserved copies of alpha tubulin in bdelloid rotifers - Eyres Isobel; Frangedakis Eftychios; Fontaneto Diego; Herniou Elisabeth A; Boschetti Chiara; Carr Adrian; Micklem Gos; Tunnacliffe Alan; Barraclough Timothy G (BMC Evolutionary Biology, 2012)
Abstract Background Bdelloid rotifers are microscopic animals that have apparently survived without sex for millions of years and are able to survive desiccation at all life stages through a process called anhydrobiosis. Both of these characteristics are believed to have played a role in shaping several unusual features of bdelloid genomes discovered in recent years. Studies into the impact of asexuality and anhydrobiosis on bdelloid genomes have focused on understanding gene copy number. Here we investigate copy number and sequence divergence in alpha tubulin. Alpha tubulin is conserved and normally present in low copy numbers in animals, but multiplication of alpha tubulin copies has occurred in animals adapted to extreme environments, such as cold-adapted Antarctic fish. Using cloning and sequencing we compared alpha tubulin copy variation in four species of bdelloid rotifers and four species of monogonont rotifers, which are facultatively sexual and cannot survive desiccation as adults. Results were verified using transcriptome data from one bdelloid species, Adineta ricciae . Results In common with the typical pattern for animals, monogonont rotifers contain either one or two copies of alpha tubulin, but bdelloid species contain between 11 and 13 different copies, distributed across five classes. Approximately half of the copies form a highly conserved group that vary by only 1.1% amino acid pairwise divergence with each other and with the monogonont copies. The other copies have divergent amino acid sequences that evolved significantly faster between classes than within them, relative to synonymous changes, and vary in predicted biochemical properties. Copies of each class were expressed under the laboratory conditions used to construct the transcriptome. Conclusions Our findings are consistent with recent evidence that bdelloids are degenerate tetraploids and that functional divergence of ancestral copies of genes has occurred, but show how further duplication events in the ancestor of bdelloids led to ...